2009
DOI: 10.1007/s00228-009-0747-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization and off-label drug use among Spanish emergency room paediatric patients

Abstract: Objective To describe the use of medicines and to determine the frequency of off-label use in emergency room paediatric patients. Patients and methods A prospective, observational and descriptive study was carried out in the setting of the paediatric emergency room of a Spanish general hospital. Medicines used by children <14 years prior to their emergency room visit were analysed based on information collected from parents/guardians and relatives for each drug prescription. Off-label use was defined as the ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
2
23
0
5
Order By: Relevance
“…Our data confirm findings which show that antiemetics display a high rate of off-label prescriptions [61]. Some studies included in this systematic review reported that antibiotics, such as amikacin [29,32,36,42], amoxicillin [21,23,25,29,38] and ceftriaxone [34,36,42], were also prescribed off-label and/or unlicenced, thus confirming previous reports that antibiotics are the most prescribed off-label and/or unlicenced drug subgroups [2,56,62,63].…”
Section: 5supporting
confidence: 94%
See 2 more Smart Citations
“…Our data confirm findings which show that antiemetics display a high rate of off-label prescriptions [61]. Some studies included in this systematic review reported that antibiotics, such as amikacin [29,32,36,42], amoxicillin [21,23,25,29,38] and ceftriaxone [34,36,42], were also prescribed off-label and/or unlicenced, thus confirming previous reports that antibiotics are the most prescribed off-label and/or unlicenced drug subgroups [2,56,62,63].…”
Section: 5supporting
confidence: 94%
“…However, other factors, such as the presence of a different formulation or contraindication, were regarded as off-label or unlicenced by different authors. Only 12 papers [19,20,28,30,32,33,35,38,39,46,49,51] accepted the definition of off-label and/or unlicenced drugs proposed by Turner et al [19]. Unlike the latter [19], some authors viewed contraindicated drugs for paediatric use as unlicenced [22,27,34,43,47,48] and drugs with a formulation other than that which had been approved as offlabel [21-25, 27, 34, 40, 41, 43, 47, 50].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…OLDU is a common practice throughout the world with rates reported to be between 18% and 36% in adults (3)(4)(5)(6) and 3%-87% in pediatric patients (7)(8)(9)(10)(11)(12)(13)(14)(15). Moreover, the incidence of OLDU may vary depending on several factors such as the healthcare facility and the disease profile (11).…”
Section: Introductionmentioning
confidence: 99%
“…Off-label prescription also varied with respect to dosage, indication, route of administration and therapeutic group [1][2][3]. Analgesics (paracetamol, ketoprofen, thiopental, fentanyl), bronchodilators (budesonide and salbutamol) and psychotropic drugs were among those medicines most frequently prescribed offlabel across countries [7][8][9][10]. Very few studies have examined the contribution of medicines used in children in an off-label or unlicensed manner to ADR occurrence [7].…”
Section: Introductionmentioning
confidence: 99%